Penggunaan Bungkil Inti Sawit Fermentasi dengan EM-4 dalam Ransum Ditinjau dari Kualitas Karkas Ayam KUB: Bungkil Inti Sawit - Harissatria; dara surtina; gunawan dwi nanda (Jurnal Peternakan Mahaputra, 2022)
This study aims to determine the use of fermented palm kernel cake with EM-4 in the ration in terms of slaughter weight, carcass weight, and abdominal fat weight of superior village chickens from Balitbangtan. The material in the study was 32 male KUB chickens aged 10 weeks, obtained from AIAT Kayu Aro. The design used was a completely randomized design (CRD) consisting of 4 treatments: P0 (given 0% BISF), P1 (given 10% BISF), P2 (administered 20% BISF) and P3 (30% BISF). Each treatment consisted of 4 cage units as replicates. Each cage unit is filled with 4 KUB chickens. The variables in this study were slaughter weight (grams/head. Carcass weight (grams/head). Abdominal fat weight (grams/head). Based on the results, it can be concluded that fermented palm kernel cake (BISF) with EM-4 can be given up to 20% in the ration of KUB chickens aged 10 weeks because it produces slaughter weight and carcass weight which is significantly higher than the slaughter weight and carcass weight due to rations without BISF and also rations with 30% BISF.